Patient satisfaction of computer guided reduction of Zygomatico-Maxillary Complex (ZMC) fractures using Patient Specific Guide (PSG) versus conventional reduction: a randomized clinical trial - Ahmed Morad; Mohamed Mounir; Usama El Dakrory; Hany Amin; Ragia Mounir (Romanian Journal of Stomatology)
Background and objectives. This study was conducted to evaluate of the patient satisfaction of computer guided reduction of Zygomatico-Maxillary Complex (ZMC) fractures using Patient Specific Guide (PSG) Versus Conventional reduction. Materials and methods. In this clinical trial patients were classified into two groups; each group consist of eight patients where the study group represented the use of patient specific guide for reduction and fixation of zygomatic fracture while the Control group represents conventional reduction and fixation of zygomatic fracture. The primary outcome is patient satisfaction while intraoperative time is the secondary outcome. Results. There was no statistical significancy in the overall satisfaction level between CR and GR, also there was no significancy between time consumed in CR and GR as guided reduction technique could save only about 8 minutes. Conclusions. Patient-specific guided reduction is an satisfactory technique for the reduction of zygomatico-maxillary complex (ZMC) fractures. Moreover, this technique decreased the operation time without a statistically significant difference from the conventional technique.